EFEKTIVITAS SENYAWA BIOAKTIF EKSTRAK KENCUR (KAEMPFERIA GALANGA L.) MENGGUNAKAN PELARUT AQUADES DENGAN PELARUT METANOL - Sri Nopita Primawati; Nofisulastri Nofisulastri; Baiq Asma Nufida (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
Kaempferia galanga L. capability as antibacterial has been proven by the formation of drag zone in some pathogenic bacteria such as Staphylococcus aureus, Streptococcus pyogenes and Klebsiella pneumonia by disc-diffusion method. The secondary metabolite content of Kaempferia galanga L., which is efficacious as antibacterial include essential oil, sesquiterpenoid, flavonoid, phenolic or polyfenol compounds and alkaloids. Therefore, it is necessary to do this research to isolate antibacterial compounds from kencur with various solvents such as aquadest with methanol. This research was a laboratory experiment with complete randomized design (RAL) with extract concentration of 50%, 75% and 100% of aquadest solvent with methanol five times repetition. Antibacterial test using agar diffusion method with wells. The inhibit zone formed is tabulated and analyzed using one-way analysis of variance (Anova). It was found that there was a significant difference between the extract with the aquadest solvent and the methanol solvent extract on Salmonella typhimurium growth at a significant level of 5% (Fcount (282.86) > Ftable (2.62)). However the drag zone formed in the weak category is below 15 mm. So it can be concluded that the extract methanol kencur showed weak antibacterial activity seen from the increase in diameter of inhibit zone of Salmonella typhimurium bacteria significantly along with increasing the concentration of methanol extract of kencur rhizome but not on the extract of aquadest Kaempferia galanga L. kale rhizome.